Hologram reconstruction corrected for measurements through layers with different refractive indices in digital in-line holographic microscopy - Sendra, Gonzalo H.; Weiße, Sebastian; Maleschlijski, Stojan; Rosenhahn, Axel (Applied optics, 2012)
Digital in-line holographic microscopy (DIHM) using point sources has been shown to be a versatile technique, especially for three-dimensional tracking of particles or microorganisms. However, the spherical source wave is altered when measurements are performed through layers with different refractive indices, such as water cuvettes. The situations where a layer of medium with a refractive index different than that of the predominant surrounding propagation medium (usually air) is situated behind or in front of the plane to be reconstructed are analyzed in detail, and a general approach for reconstruction under such circumstances is developed. The proposed refractive index correction is tested experimentally and compared to conventional reconstruction algorithms. Using 3D traces of swimming algal spores, the influence on the velocity calculation is also shown.
Gesehen am 05.07.2018